Sosialisasi Peningkatan Pemahaman Mahasiswa KKL Prodi Pendidikan Geografi, STKIP PGRI Sumatera Barat dalam Memanfaatkan Sabut Kelapa menjadi Keset - Nefilinda; Slamet Rianto; Arie Zella Putra Ulni; Momon Dt Tanamir; Loli Setriani (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose service is carried out to utilize coconut belt waste so that it can beutilized andeven have economic value. This activity is asocialization involving students from the Geography Education Study Program and the community in Nagari Sungai Sariak, to be able to utilize coconut coir waste. There sult sof community service regarding the socialization of theuse of coconut coir waste to improve the welfare of Nagari Sungai Sariak are in the for mofdoormats. Doormat products can beused for house hold needs and even sold to increase the welfare of the community.